EFFECT OF INCUBATION ON SPERM MOTILITY AND LIVABILITY OF LABRADOR RETRIEVER DOG SPERMATOZOA PRESERVED AT 5ºC IN DIFFERENT EXTENDERS - DAS, A; BISWAS, R K; DEKA, B C (The Indian Journal of Animal Reproduction, 2017)
Four ejaculates from each of two adult Labrador Retriever dogs collected by digital manipulation method wereextended @ 1:4 in Tris-Egg Yolk-Citric Acid-Glucose (TEYCAG), Tris-Egg Yolk-Citric Acid-Fructose (TEYCAF) andEgg Yolk-Citrate-Glycine-Glucose (EYCGG) extender by split sample technique. The extended semen sampleswere preserved at 50C for 24, 48, 72 and 96h. Thereafter, the aliquots of preserved semen samples were incubatedat 37oC for 0, 2, 4, 6 and 8h. Irrespective of preservation period and incubation period, the mean sperm motilityand live sperm percentage differed (p0.05) between TEYCAG and TEYCAF extenders. Mean sperm motilityand live sperm percentage were higher (p
Keywords: Incubation; Labrador -Retriever dog; live sperm; semen preservation; sperm motility